Pendampingan UMKM Perikanan dalam Pengolahan Ikan Nila menjadi Produk Siap Konsumsi di Desa Kadubeureum - Arianto, Bambang; Jikhan, Fat’Chatus Chanifa (Welfare : Jurnal Pengabdian Masyarakat, 2025)
This community service aims to increase the capacity of parrot fish farmers in implementing diversification strategies and innovation of processed tilapia products. This aspect is very much needed because of the needs of farmers in facing increasingly competitive market challenges, as well as opportunities for developing more innovative and high-value tilapia-based products. In the community service in Kadubeurem Village, Padarincang, Serang Regency which was carried out on June 10th 2023, training and mentoring were provided. The implementation method includes interactive discussion sessions and practical simulations, so that participants are given insight into tilapia product diversification techniques, such as processing fishery products into ready-to-consume products. The success of this program can be seen from the achievement of participants' understanding of the material presented, the implementation of innovation by farmers, and the increase in income from product diversification. This activity also shows that tilapia farmers have been able to adopt innovative techniques in tilapia cultivation and processing, which has an impact on increasing the selling value and competitiveness of products.